1992
DOI: 10.1089/neu.1992.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Helper T-Cell Function Following Severe Head Injury

Abstract: Major infections, such as sepsis and pneumonia, occur in 50-75% of patients following isolated severe head injury. Previous studies have demonstrated that this high incidence of infection following severe head injury may be related to a decrease in helper T-cell activation and function. The present study was designed to investigate the effect of severe head injury on specific subgroups of helper T cells known to enhance or suppress cellular immune function. Specifically, peripheral blood lymphocytes (PBLs) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…In addition, HDL particles reverse the inhibitory action of oxidized LDL particles on endothelium-dependent arterial relaxation [41] and also inhibit cytokine-induced expression of endothelial cell adhesion molecules [42]; both of which may be potential mechanisms in the development of VaD. Oxidative stress and lipid oxidation in particular have a pivotal role in the development of VaD [43]; lipid peroxidation may influence neuronal membrane permeability, affecting cellular function and damaging membrane-bound receptors and enzymes [44]. The brain may be particularly susceptible to oxidative lipid damage due to its high content of polyunsaturated fatty acids [44].…”
Section: Lipid Effects On Vascular Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HDL particles reverse the inhibitory action of oxidized LDL particles on endothelium-dependent arterial relaxation [41] and also inhibit cytokine-induced expression of endothelial cell adhesion molecules [42]; both of which may be potential mechanisms in the development of VaD. Oxidative stress and lipid oxidation in particular have a pivotal role in the development of VaD [43]; lipid peroxidation may influence neuronal membrane permeability, affecting cellular function and damaging membrane-bound receptors and enzymes [44]. The brain may be particularly susceptible to oxidative lipid damage due to its high content of polyunsaturated fatty acids [44].…”
Section: Lipid Effects On Vascular Dementiamentioning
confidence: 99%
“…Oxidative stress and lipid oxidation in particular have a pivotal role in the development of VaD [43]; lipid peroxidation may influence neuronal membrane permeability, affecting cellular function and damaging membrane-bound receptors and enzymes [44]. The brain may be particularly susceptible to oxidative lipid damage due to its high content of polyunsaturated fatty acids [44]. Paraoxonase 1 is an A-esterase with peroxidase-like activity present on the surface of HDL, which decreases peroxidation of LDL.…”
Section: Lipid Effects On Vascular Dementiamentioning
confidence: 99%
“…Head injury is followed by an almost immediate drop of lymphocyte numbers that is accompanied by a deficit in T-cell activation and decreased CD25 expression. These changes seem to persist up to several weeks after TBI [21,34,35]. β2m is a small glycoprotein and elevated levels of the soluble form are thought to reflect the release by activated lymphocytes and neutrophils [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, T-cell numbers and function remain suppressed for up to 3 weeks after injury [21,34,35]. However, elevations of sIL-2R and neopterin, representing a sustained activation of the IFN-γ and TNF pathways, are not necessarily synonymous for an efficient immune response [36].…”
Section: Discussionmentioning
confidence: 99%
“…After severe head injury, decreased T-helper cell activation, attenuated lymphokine-activated killer cell cytotoxicity, and depression of proinflamma-tory cytokine production (IL-2, IFN-␥), have been reported. [9][10][11][12][13][14] Moreover, ex vivo whole blood stimulation with lipopolysaccharide (LPS) shows an attenuated production of proinflammatory cytokines TNF␣, IL-1␤, IL-6, IL-8, IFN-␥, and IL-12 in polytrauma patients compared to healthy controls. 15 Another study demonstrated decreased TNF␣ mRNA levels in human peritoneal macrophages after polytrauma, while the antiinflammatory cytokine IL-10 was upregulated.…”
Section: Immune Paralysis In Patients With Tbimentioning
confidence: 99%